The phantom music box - Weyn, Suzanne (Weyn, Suzanne. Haunted Museum, 2014)
Emma would rather be at her ballet class than at the Haunted Museum, but she can't miss her best friend's birthday party. In a spooky exhibit of music boxes, she's drawn to one in particular, in which a pair of dancers spin slowly to a haunting melody. But that very night, the music box shows up at her door--like it's following her. Emma dances better than she ever imagined when the music box is playing. But that's not all. Sometimes the music speeds up, and the dancers seem to move on their own. Emma finds the lid open, music playing, even when she knows she'd shut it before. And then an eye appears in the mirror inside the lid--someone is watching Emma! The more Emma learns about the history of the music box, the more she realizes she needs to break the hold it has over her before it's too late. But the better she dances when the music plays, the less she wants to!